A new invasive species Proagopertha lucidula (Faldermann, 1835) (Coleoptera, Scarabaeidae, Rutelinae) for Kazakhstan - Izbasar I. Temreshev (Acta Biologica Sibirica, 2025)
Shining leaf chafer Proagopertha lucidula (Faldermann, 1835) is firstly found in Kazakhstan. Records in South-East Kazakhstan (Almaty and Zhetysu oblast) are the westernmost for this species. This species causes damage in the fruit orchards of the Almaty and Zhetysu oblast.